Pengaruh Konflik Dan Stress Kerja Terhadap Kinerja Karyawan - Ardiansyah, Reza; Samsudin, Acep; Prabowo, Budi; Huda, M. Zidhan Nurul; Siregar, Muhammad Rafi (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research investigates factors that have an important impact on organizations such as work conflict and work stress. We analyzed five international journals that are relevant to understanding work conflict and work stress in various organizational contexts. The results of the analysis show that the perceived work stress, it is stated that employees experience psychological disorders and really threaten their health when they are busy working. Employees with high levels of stress in the face of excessive workloads can experience burnout and intend to stop working. Employees who experience job insecurity cannot show their true performance and cannot obtain the desired efficiency from employees because they do not see themselves permanently in their organization. However, the expected efficiency cannot be achieved because employees who have role conflicts have to fulfill more than one workload. Employees who are satisfied with their organization are able to adopt the organizational culture and develop their organizational skills such as planning and problem solving.